(untitled) (Cardiovascular Journal, 2013)
Percutaneous coronary intervention is being performed over the last 35 years. In this time span a remarkable advancement occurred in this field regarding skill & hardware. Its spectrum has also been widened starting from chronic stable angina to Acute coronary syndrome, single vessel disease to multivessel disease, simple to complex lesions including left main disease. The incidence and prevalence of Ischaemic heart disease (IHD) is also increasing. Number of studies has been conducted to decide how far this modality of treatment can change the morbidity and mortality of the IHD. Cardiologists are trying to detect the culprit lesions, treatment of which will be beneficial for the patient. Number of noninvasive and invasive modalities has been introduced to determine the functional significance of a coronary artery stenosis. Fractional flow reserve (FFR) is one of the relatively new methods in this field. We will discuss some of the basic aspects of FFR and its implications in different subsets of coronary artery disease. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14324 Cardiovasc. j. 2013; 5(2): 190-200